Impact of medical record quality on discharge waiting time at private teaching hospitals in Mashhad, Iran - Gommnami, Nasser (2016)
Patient documentation is central to patient care. Proper documentation effects on safety and continuing of care. Incomplete patient records ranged from 22 to 100% in Iranian hospitals and resulted to increased patient length of stay and increased discharge waiting time. Medical record quality consisted of four components; reliability that used for stability and consistency of data, accessibility of patient data that essential for risk management and healthcare costs, accuracy for coding and lastly completeness of the medical record. The study aims to determine the impact of medical record quality on discharge waiting time in private teaching hospital. Methodology: An intervention study was carried out at two private teaching hospitals in Mashhad Iran, whereby pre, post and follow up intervention measurement were taken. Hospitals had two matched wards; that are male and female wards with surgical and internal medicine patients. Sample size was 146. After discharge ordered by doctor measurements on discharge waiting time were recorded in the pro-forma with 7 items, and medical record quality components with 69 items that were adopt from patient records and previous studies also recorded as a base-line data. The intervention was arranged totally 6 sessions for physicians and medical students at intervention hospital to ensure them to fulfilment elements of medical records quality components that is; completeness, reliability, accuracy and accessibility on patients‟ records. The intervention was in the form of workshops, lectures, reminders and official letters, face to face feedback based on prepared protocol. Post intervention and follow-up data on discharge waiting-time and medical record quality components were taken with interval of 5 months. The data analysed by SPSS 19. Results: Totally 979 questionnaires were accepted from two hospitals. The average of response rate was 96.8 and 94% in intervention and control hospital respectively. Totally 537 (55%) of respondents were female. The length of stay was 1.84±1.81 days, age were 39.21±20.43 years. Wednesday was the busiest day for discharge (19.20%). All medical record quality components and discharge waiting time were normally distributed. The completeness of records had the highest score (3.90±0.35) and followed by reliability was 3.37±1.05, accuracy was 2.71±0.87 and accessibility was the lowest score (2.56±0.83) among medical record quality components. Discharge waiting time was 2.74±1.37. Medical record quality components and discharge waiting time were no significance differences between intervention and control hospital during base line (P>0.05), except for accuracy (P<0.001). After third stages assessment all medical record quality components and discharge waiting time were statistically significance in intervention and control hospital. Analysis of variance of the medical record quality components and discharge waiting time showed that; reliability (P<0.001), accuracy (P<0.001), completeness (P<0.001), accessibility (P<0.01) and discharge waiting time (P<0.04), all variables were statistically significant. The multiple regression analysis revealed completeness and accessibility were associated with discharge waiting time in intervention hospital (ß=-0.09 & ß=0.11) (F=4.54, P= 0.001). The MANCOVA analysis in intervention and control hospital, after adjusting for age, gender, length of stay and ward demonstrated that hospital, time and interaction were significant (P<0.001) with large effect size (0.58 & 0.61) and among adjusted variables gender was significant (P=0.01) with small effect size (0.24) Conclusion: Medical record needs quality indicators for the improvement of patient medical history. Medical record quality needs continuous assessment in Iranian hospitals and this study‟s results propose new intervention methods. Completeness for patient records and discharge summary still need improvement and physicians should be involved in this procedure. The study described that discharge waiting time in private teaching hospital is similar to private sector and was less than public hospitals. The study revealed that discharge waiting time could be predicted by two of the medical record quality components; completeness and accessibility. There are a lot of issues in patient discharge delay view point of time, costs and clinic that are recommended for future studies.